Model Discovery Learning dengan Pendekatan Saintifik untuk meningkatkan keaktifan siswa Madrasah Aliyah dalam pembelajaran Matematika - Maharani, Febrita Syafitri (MAN 4 Kota Pekanbaru, 2023)
One of the factors that cause student learning outcomes to be low in mathematics is the need for more student activeness in learning. The Discovery Learning Model aims to train critical, scientific, and analytical thinking skills. Thus, students are expected to be able to find their mathematical structures. This article aims to improve the activeness of class X MAN 4 Kota Pekanbaru students through a Discovery Learning Model with a Scientific Approach. The method used is action research on students in classes with 70 samples. The research was conducted over two cycles, each comprising four stages of activities. Data were collected through observation, documentation, and interviews and then analyzed using qualitative descriptive analysis techniques. The results showed that this model could improve the student’s learning activeness. Several recommendations can be made to improve student activeness, including explaining the learning objectives, creating discussion groups, and giving rewards to students. However, for more optimal results, it is important to increase the provision of exercises to the students.